2014
DOI: 10.1088/2040-8978/16/10/105007
|View full text |Cite
|
Sign up to set email alerts
|

Super-focusing of visible and UV light using a meta surface

Abstract: In this paper, a novel meta surface is proposed for super-focusing. This surface contains two slits surrounded by finite corrugations for enhanced focusing. This simple surface has the super-focusing ability to focus both near and far field light in a hot-spot with an FWHM much smaller than half the wavelength of the incident light. The structure is suitable for one dimensional and two dimensional focusing applications. The enhanced transmission through the double slit is also utilized for directional beaming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…In this study, we proposed an optical grating sensor based on dielectric material which is silicon dioxide (SiO2) used as the substrate and silicon (Si) as the top layer of the grating. This structure was previously introduced using epoxy and silicon nitride (Si₂N₃) materials for a visible and infrared range of wavelengths [21]. The same wavelength is used here but with the proposed materials.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we proposed an optical grating sensor based on dielectric material which is silicon dioxide (SiO2) used as the substrate and silicon (Si) as the top layer of the grating. This structure was previously introduced using epoxy and silicon nitride (Si₂N₃) materials for a visible and infrared range of wavelengths [21]. The same wavelength is used here but with the proposed materials.…”
Section: Introductionmentioning
confidence: 99%
“…Metamaterial paved the way for numerous applications such as optical sensors [16], super focusing [17] and energy harvesting [18]. Metasurfaces (MS) are special class of metamaterial that is composed of engineered subwavelength nanoresonators [15], [16], [19]- [21]. MSs have been widely explored providing Fano spectral lines for diverse of including optical sensors [11], [13], [22], [23].…”
Section: Introductionmentioning
confidence: 99%
“…First, PM6 has higher photo current (high extication coefficient of both PM6 and Y6),high fill factor and low energy loss. It has a large bandgap of 1.80ev, a strong absorption spectrum of 500nm-700nm, and the highest occupied molecular orbital (HOMO) energy level of -5.54ev that obtained high open circuit voltage second, Y6 has a narrow optical bandgap of 1.33ev, strong nearinfrared light absorption, absorption onset located at 931nm and the highest o ccupied molecular orbital (HOMO) and low unoccupied molecular orbital (LUMO) energy levels at-5.65ev and -4.10ev [10][11][12][13][14][15]. PM6 andY6 blend with absorption bands in visible and near-infrared regions.introducing abroad spectral response in external quantum efficiency (EQE) ranging from 450nm to 830nm.by the study of PM6:Y6 in one blend, the electrostatic interface field for Y6 is large to compensate for the coulomb dissociation barrier and thus enabling barrier -free dissociation [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Durrant found that composing of PM6:Y6 show a narrow distribution of electronic trap states than other organic blend systems studied and the intra-band gap states(low energetic disorder),low the energetic losses including charge carrier traping into any state that enhance device performance and confirms uniformity and rigidity which enhance carrier dynamics, enable efficient charge generation, reduce the voltage losses in this low energy offset system and reduce charge recombination to Y6 which make this blend has high performance [20][21][22]. Such materials described by non-ideal band edges with significant density of states ,this materials including the presence of tail states(shallow trap states)extending into the bandgap.the tail states have some charactristics like trap depth and density that effect on the devive performance of organic solar cells devices [12][13][14].for example charge trapping into any state effect on charge transport and inc rease recombination.To enhance the absorption of the PM6:Y6 active layer, plasmonic nanoparticles (NPs) and refractory metals play an important role to boost the PCE of OSCs [11][12][13][14][15][16][17][18][19][20]. The most used Plasmonic NPs in literature were gold (Au) and silver (Ag) embedded into one of the OSC layers like the active layer [21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%